Bibliografía española de Derecho penal (abril 2005-octubre 2005) - Higuera Guimerá, Juan Felipe; Alastuey Dobón, Carmen; Escuchuri Aísa, Estrella; Rueda Martín, María Ángeles; Vizueta Fernández, Jorge; Mayo Calderón, Ana Belén; Fernández Ibáñez, Eva (Revista de Derecho Penal y Criminología, 2019)
-